Representações da maternidade no ativismo de nascimento em Portugal e na Europa: velhos arquétipos ou novos sujeitos políticos? - Neves, D. M. (VIII Congresso da APA, 2022)
This presentation results from a research on childbirth activism in different European contexts, where I explore the emergence and the ways of action of social movements advocating for the humanization of childbirth and women’s rights in pregnancy and childbirth. Based on documental analysis and on preliminary results of the fieldwork carried out in recent years in Portugal and in other European countries, this presentation will bring to light affinities and controversies that cross social movements, reflecting different conceptions of motherhood and different ways of understanding the role of women in societies. In this way, we will seek to comprehend how does childbirth activism conceive the social functions of motherhood and how - from the essentialization of the woman to her acknowledgement as a political subject par excellence - different perspectives take place, reinforcing alliances and ruptures between social movements.